2015
DOI: 10.1179/1945577115y.0000000006
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan to reduce cardiovascular risk in older HIV-infected adults: a pilot study

Abstract: Background HIV-infected persons are at increased cardiovascular disease (CVD) risk, but traditional CVD therapies are understudied in this population. Telmisartan is an angiotensin receptor blocker and PPAR-γ agonist that improves endothelial function and cardiovascular mortality in HIV-uninfected populations. We assessed the effects of telmisartan on endothelial function in older HIV-infected persons at risk for CVD in a small pilot study. Methods HIV-infected individuals ≥50 years old on suppressive antire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Different results have been published with heterogeneous conclusions depending on the ARB used or the marker studied [9]. The studies with ARBs in PLWH published so far investigated the effect of antagonizing angiotensin in people living with HIV‐associated nephropathy in a mice model [15] and, in humans, two pilot studies assessed cardiovascular risk and visceral fat after intervention with telmisartan [16,17]. We performed a 48‐week study with the maximum dose of losartan used for hypertension (100 mg) added to the strategy of changing the third antiretroviral agent to raltegravir.…”
Section: Discussionmentioning
confidence: 99%
“…Different results have been published with heterogeneous conclusions depending on the ARB used or the marker studied [9]. The studies with ARBs in PLWH published so far investigated the effect of antagonizing angiotensin in people living with HIV‐associated nephropathy in a mice model [15] and, in humans, two pilot studies assessed cardiovascular risk and visceral fat after intervention with telmisartan [16,17]. We performed a 48‐week study with the maximum dose of losartan used for hypertension (100 mg) added to the strategy of changing the third antiretroviral agent to raltegravir.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Angiotensin receptor blockers have also been evaluated in PWH, to assess their potential benefits in reducing endothelial injury. After a 3-month prospective study, telmisartan administration led to an increase in endothelial progenitor cells, but had no effect on immune activation (162)(163)(164). (iv) Ixolaris, a TF inhibitor that blocks the extrinsic coagulation pathway at its origin, is a promising candidate for the treatment of hypercoagulation in PWH.…”
Section: Targeting Hypercoagulation In Pwh As An Adjunct Intervention...mentioning
confidence: 99%
“…PLWH have high plasma renin activity, possibly related to the structural similarity between renin and HIV-protease, production of renin by CD4 þ T cells stimulated by HIV-1, and reninstimulated viral reproduction [50,[56][57][58]. Several small trials of telmisartan, an angiotensin receptor blocker and peroxisome proliferator-activated receptor-g agonist, showed impressive blood pressure reductions [59][60][61]. A study of losartan demonstrated decreased blood pressure but no improvement in inflammation or T-cell recovery [62 & ].…”
Section: Hypertensionmentioning
confidence: 99%